1988
DOI: 10.1007/bf02535519
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cardiac membrane phospholipid peroxidation kinetics as malondialdehyde: Nonspecificity of thiobarbituric acid‐reactivity

Abstract: When exposed to xanthine oxidase (superoxide)-dependent, iron-promoted Fenton chemistry, purified cardiac membranes evidenced, by the thiobarbituric acid (TBA) test, a virtually instantaneous peroxidative response with a maximal linear rate of 5.8 nmol malondialdehyde (MDA)-equivalents/mEquivalents lipid ester reacted/min. Yet when the lipids purified from these same membranes and reconstituted into liposomes were peroxidized under identical reaction conditions, the TBA test indicated that a pronounced (approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 41 publications
0
35
1
Order By: Relevance
“…We interpret these data to indicate that NOE inhibits MDA production by iron-induced lipid peroxidation primarily or only if the lipid substrate is the component of a membrane. It is also possible that free radical-induced peroxidation of cardiac mitochondria yields some nonlipid-derived TBA- reactive substances other than MDA, as was recently demonstrated with rat heart membranes [16]. Our present data do not indicate whether NOE acts as a free radical scavenger, stabilizes mitochondrial membranes against free radical attack, or inhibits the chain reaction leading to MDA.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…We interpret these data to indicate that NOE inhibits MDA production by iron-induced lipid peroxidation primarily or only if the lipid substrate is the component of a membrane. It is also possible that free radical-induced peroxidation of cardiac mitochondria yields some nonlipid-derived TBA- reactive substances other than MDA, as was recently demonstrated with rat heart membranes [16]. Our present data do not indicate whether NOE acts as a free radical scavenger, stabilizes mitochondrial membranes against free radical attack, or inhibits the chain reaction leading to MDA.…”
Section: Resultscontrasting
confidence: 48%
“…Because the TBA-reactivity assay is not specific for MDA, this method may also include certain other oxidation products [16].…”
Section: Methodsmentioning
confidence: 99%
“…The TBA reaction has frequently been used for measuring lipid peroxidation in biologic samples but has limitations because a part of the TBA-positive material does not originate from lipid peroxides. 29 Nevertheless, change in TBARS level remains a reliable index of lipid peroxidation, especially in comparative studies made on the same biologic material. In brain homogenates incubated under aerobic conditions, Rehncrona et ai 23 have shown that increases in TBARS level were correlated with the loss of polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of thiobarbituric-acid-reactive substances (TBARS) was calculated using the absorption coefficient 1.56 X lo5 M-' cm-' [31]. This measurement may include TBARS arising from non-lipid sources [32].…”
Section: Determination Of Ca2+ Fluxesmentioning
confidence: 99%